Optimization of batch process plant (software development) / Lob Muhammad Abdul Shukur - Abdul Shukur, Lob Muhammad (1996)
This thesis looks at ways in which more enhanced computer control can be provided in the batch process industries. Proposals are made for a system with folly integrated facilities. These proposal cover the performance enhancement of batch plant based on graph theory, batch process modelling by mean of timed Petri Nets, control and optimization based on dynamic programming and the principle of optimality. The method adopted here is to find these optimal values by using dynamic programming method. Dynamic programming is a method for the optimization or mathematical representation of systems in which one works by stages or sequences using the principle of optimality. By proper application dynamic programming can cut across all the fields of mathematical programming. Therefore optimization of a batch process plant is proposed.